Americanizing Britain the rise of modernism in the age of the entertainment empire - Abravanel, Genevieve, 1975- (Oxford : Oxford University Press, 2012)
Americanizing Britain anatomizes the various ways British writers responded to the ever-increasing influence of U.S. culture on Britain and the rest of the world.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes index.
Keywords: English literature -- 20th century -- History and criticism; Modernism (Literature) -- Great Britain; English literature -- American influences; United States -- Civilization -- 1918-1945.; United States -- In literature